Microanatomical Studies on the Testis of the Emu (Dromaius novaehollandiae) - Rajendranath, N; Rao, T S Chandrasekhara; Kumar, D Pramod; Raghavendar, K B P; kumar, V Girish (Indian Journal of Veterinary Anatomy, 2018)
The testes of emu were enclosed by a thick capsule consisting of an outer tunica serosa, middle fibrous layer and inner tunica vasculosa. Despite the presence of small amount of septa there was no distinct lobulation of the testis Melanocytes scattered in the capsule and interstitial tissue were responsible for the dark coloration of the testes. The seminiferous tubules were lined by a stratified epithelium and showed two basic cell types: sertoli cells and spermatogenic cells. During breeding season, the seminiferous tubules had wide tubular diameter and showed very thick germinal epithelium. The testicular morphology changed markedly during non breeding season. The testes showed intense to moderate PAS reaction. Breeding season testes showed moderate reaction for cholesterol in Leydig cells. The Alkaline phosphatase (AKP) and Acid phosphatase (ACP) activities were intense in testes.